Chemical optimization of siRNA for safe and efficient silencing of placental sFLT1 - Sarah M. Davis; Vignesh N. Hariharan; Agnes Lo; Anton A. Turanov; Dimas Echeverria; Jacquelyn Sousa; Nicholas McHugh; Annabelle Biscans; Julia F. Alterman; S. Ananth Karumanchi; Melissa J. Moore; Anastasia Khvorova (Elsevier, 2022)
Preeclampsia (PE) is a rising, potentially lethal complication of pregnancy. PE is driven primarily by the overexpression of placental soluble fms-like tyrosine kinase 1 (sFLT1), a validated diagnostic and prognostic marker of the disease when normalized to placental growth factor (PlGF) levels. Injecting cholesterol-conjugated, fully modified, small interfering RNAs (siRNAs) targeting sFLT1 mRNA into pregnant mice or baboons reduces placental sFLT1 and ameliorates clinical signs of PE, providing a strong foundation for the development of a PE therapeutic. siRNA delivery, potency, and safety are dictated by conjugate chemistry, siRNA duplex structure, and chemical modification pattern. Here, we systematically evaluate these parameters and demonstrate that increasing 2'-O-methyl modifications and 5' chemical stabilization and using sequence-specific duplex asymmetry and a phosphocholine-docosanoic acid conjugate enhance placental accumulation, silencing efficiency and safety of sFLT1-targeting siRNAs. The optimization strategy here provides a framework for the chemical optimization of siRNAs for PE as well as other targets and clinical indications.